Understanding the Drivers of Investment Intention: A Systematic Literature Review - Atmaya Fitra Alfathya; Sumiati; Nur Khusniyah Indrawati (PT FORMOSA CENDEKIA GLOBAL, 2025)
The increasing accessibility of financial markets has created more opportunities for individuals to invest, yet participation rates remain low in certain regions. This study examines key factors influencing investment intentions through a systematic literature review guided by the PRISMA framework, analyzing 44 articles. The findings classify investment intention determinants into five categories: personal, psychological, company-related, social, and technological. Financial literacy, the TPB’s component, and perceived risk are the most frequently discussed and significantly impact investment intention. Additionally, social media and influencers play a crucial role in enhancing financial awareness and information dissemination, thereby encouraging individual investment intentions. The growing interest in sustainable investment also opens new opportunities for individual investments. These results have significant implications for the development of investment intention literature and offer practical guidance to policymakers and financial institutions in formulating strategies that enhance individual investment intentions.